1991
DOI: 10.1038/bjc.1991.417
|View full text |Cite
|
Sign up to set email alerts
|

The detection of phthalocyanine fluorescence in normal rat bladder wall using sensitive digital imaging microscopy

Abstract: Summary The ability to detect photosensitisers in tissue at a microscopical level is important when studying photodynamic therapy (PDT) in both normal and malignant tissue. We have studied the fluorescence distribution of aluminium sulphonated phthalocyanine (AlSPc) in the normal rat bladder using a cooled CCD (charge coupled device) imaging system with computerised image processing. This system makes it possible to carry out a quantitative assessment of photosensitiser fluorescence in the various layers of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Since most porphyrins exhibit a characteristic red fluorescence, their tumour-localising properties can be used for tumour detection (Lipson et al, 1967;Pope et al, 1991). The photosensitising properties of porphyrins, together with their tumour-localising properties, were first exploited for therapeutic purposes by Auler and Banzer (1943).…”
mentioning
confidence: 99%
“…Since most porphyrins exhibit a characteristic red fluorescence, their tumour-localising properties can be used for tumour detection (Lipson et al, 1967;Pope et al, 1991). The photosensitising properties of porphyrins, together with their tumour-localising properties, were first exploited for therapeutic purposes by Auler and Banzer (1943).…”
mentioning
confidence: 99%
“…Sensitive fluorescence microscopy of frozen sections taken after sensitisation with phthalocyanine has demonstrated localisation of fluorescence to well-vascularised areas of stroma in the rat colon (Barr et al. 1988), rat bladder (Pope et al, 1991a), and hamster pancreas (Chatlani et al, 1992). Using a radioactive microsphere technique, blood flow to transplantable bladder tumours has been shown to be markedly reduced after treatment with chloroaluminium tetrasulphophthalocyanine and light (Selman et al, 1986), indicating that HPD and phthalocyanines have similar effects on the microvasculature.…”
mentioning
confidence: 99%
“…Recent experimental studies with the second generation photosensitiser, disulphonated aluminium phthalocyanine, AlS2Pc, using fluorescence microscopy, have shown that this photosensitiser is highly concentrated in the vasculature of normal rat colon and bladder 1 h after administration Pope et al, 1991). This has also been shown for DMH-induced colon tumours in rats (P.T.…”
mentioning
confidence: 76%
“…They were snap frozen in liquid nitrogen, and two serial cryostat sections were taken (10 tm slices) from each tumour, one section for staining with haematoxylin and eosin and the other for fluorescence microscopy analysis using a cooled charge-coupled device (CCD) (Barr et al, 1988;Pope et al, 1991). A slightly modified technique was used as described by Chatlani et al (1991).…”
Section: Histology Andfluorescence Microscopymentioning
confidence: 99%